'Where the Wild Things Are': Etruscan Hunting and Trophy Display at Poggio Civitate (Murlo), Italy. (February 2023) - Kansa, Sarah Whitcher; Tuck, Anthony
Abstract : An integrated study of the zooarchaeological, iconographic, and artefactual data from the Etruscan site of Poggio Civitate (Murlo, Italy), inhabited from the eighth to the sixth century bc, reveals intra-site differences in the distribution and disposal of animal body parts and species represented, including wild animals. Smaller mammals and birds that would be trapped are encountered more frequently in the site's workshop area and larger prey (deer, wolf, bear, and aurochs) that would be hunted are found more often in the area of the elite residence. We suggest that some of these remains are evidence that hunting was for the purpose of trophy display by the elites of Poggio Civitate and we discuss the social implications of such an activity in this community.